G633(P) Nurses' role in promoting maternal and children's oral health: Key messages from a Systematic Review. (27th April 2016) - Ibrahim, R; Blair, M
Abstract : Background: Worldwide, oral diseases contribute to a major public health burden. Oral health disparities exist amongst vulnerable groups such as children, particularly, in underserved populations. Considering the strong oral-systemic health link more emphasis should be put on oral health promotion. Objective: To assess the effectiveness of integrating promotion of oral health of young children and their mothers into nursing practice. Methodology: Search Strategy: A rigorous search of literature was performed on 1st of July, 2015 to retrieve relevant studies from seven electronic databases including CENTRAL, EMBASE, MEDLINE, GLOBAL HEALTH, CINHAL, Scopus, and Web of Science. For locating grey literature searching for conference proceedings and theses was undertaken via ProQuest. Selection Criteria: All RCTs, cluster RCTs, non- RCTs and observational studies assessing one or more preventive interventions delivered by nurses for improving oral health of young children or women in child bearing age were included. (See Figure 1 ). Results: Search Results: 3152 records were identified through electronic database searching. In addition 10 studies were retrieved from reference lists. Only 21 relevant trials were reviewed of which 12 were RCTs. Results of Data Synthesis: Participants: Numbers ranged from 94 to 4360 caregivers of young children. Gender: Proportions of boys ranged from 49% to 58%. Thirteen studies targeted poor underserved populations. Interventions Oral health education was used in all interventions, using videos or oversized models or via leaflets or pamphlets. Fluoride varnish, however, was applied in only four studies. In six studies the intervention was a one off session. The longest duration was three years (2 studies). Outcomes: Eighteen programs reported significant positive outcomes including either reduction in caries experience, better oral hygiene and dietary habits or increased rates of dental visits amongst young children or their mothers. Conclusions: There is moderate evidence that arming nurses with basic oral health competencies can have an impact on reducing oral health inequalities by contributing to a downward trend in caries experience and increased access to dental care particularly amongst poor disadvantaged populations.